Забезпечення публічної безпеки як система - Сокуренко, В. В.; Sokurenko, V. V.; Valerii Sokurenko (Вісник Кримінологічної асоціації України. - 2017. - № 2 (16). - С. 21-28, 2017)
У статті проаналізовано та виділено дві ключові цілі забезпечення публічної безпеки: охорона і захист громадян від загроз публічній безпеці. Визначено основні завдання забезпечення публічної безпеки.

The author of this article has studied one of the relevant issues of combating crime, namely systemically important objectives of ensuring public safety. It is advisable to admit guaranteeing of social and personal peace as the general objective in ensuring public safety. It is based on maintaining a balance between existing and potential threats and current and possible state of protection from them, due to which we ensure normal progressive development of social groups and the state’s population in the whole, the implementation of constructive human potential and functionally able parameters of the activity of the system of specialized subjects of population protection from the threats (their neutralization and prevention) of manmade, criminogenic, other anthropogenic and natural deterministic nature. The complex and multifaceted nature of the general objective of ensuring public safety makes it possible to distinguish its two key objectives: 1) protection of citizens against the threats of public safety, achievement of which involves forecasting the likely occurrence of the factors of danger and their timely elimination; 2) protection of citizens from the threats of public safety, the implementation of which means guaranteeing the timely termination of destructive factors of danger, elimination of the negative consequences of their actions. The need to ensure its structuring, vector specification, harmonious functioning, offensive in the work, makes it necessary to allocate tasks in ensuring public safety that can be presented in the following order: 1) continuous and timely provision of information to the moderators of the systems of ensuring public safety on the threats of its state, as well as concerning its newest types and forms; 2) prediction of probable scenarios of the development of potential and existing threats, and functional parameters of the system to counteract them; 3) planning of measures; 4) immediate implementation of preventive measures; 5) elimination (minimization, compensation) of the caused damage to public relations in the sphere of public security as a result of destructive factor, in particular criminogenic one.

В статье проанализированы и выделены две ключевые цели обеспечения публичной безопасности: охрана и защита граждан от угроз публичной безопасности. Определены основные задачи обеспечения публичной безопасности.
Обеспечение публичной безопасности как система
Ensuring public safety as a system
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; публічна безпека; забезпечення публічної безпеки; загрози; захист публічної безпеки; охорона публічної безпеки; public safety; objectives; tasks; threats; protection; defense; публичная безопасность; угроза; защита публичной безопасности; охрана публичной безопасности